Agro-Processing as a Value Added Tool to Food Production in Nigeria - Pamwal, Ephraim Fomyol; Tata, L. A. (NIU Journal of Humanities, 2019)
A paper on agro processing: adding value to food production in Nigeria highlights food security due to post-harvest losses and how to overcome it. It emphasizes on the need to process and preserve the food and non-food components. The paper is divided into six parts which include introduction, types of agro-processing, adding commercial value to raw or semi-produced food products, popularization of production, challenges in food processing in Nigeria, role of government organizations, recommendations and conclusion. In conclusion, the researchers emphasized that food security can only be achieved by processing, preserving and preventing pests and microbial contamination of food and even agricultural products and recommend the establishment of post-harvest department units. Keywords: Agro - processing, value added tool,food production and Nigeria